Effect of replacement of barley with reconstituted bajra grains (Pennisetum typhoideum) and mustard-cake with uromalt-40 on the performance of growing crossbred calves - Kundu, Ramphal; Lohan, O P (The Indian Journal of Animal Sciences, 2012)
A growth trials of 120 days on 16 growing crossbreed calves was conducted to evaluate uromalt-4U and reconstituted bajra grains. The calves were divided in 4 groups having 4 claves in each group and were fed 4 different rations. Group 1 was offered control ration T1 : in T2 barley was replaced with reconstituted bajra grains: in T3 barley was replaced with raw bajra grain, and in T4 group mustard-cake was replaced with uromalt-40. The average DM and CF intake were higher in uromalt-40 fed group. CP, EE and NFE digestibilities were significantly (P<0.05) higher in T1 and T4 treatments as compared to T2 and T3 treatment, whereas DM digestibilities was not affected due to experimental rations. CF digestibility was significantly (P<0.05) higher in T4 treatment than those of T1, T2 and T3 treatments. The blood NH3-N and blood urea-N were significantly (P<0.05%) higher in 2 and T4 treatments, in comparison to other treatment. In uromalt 40 group (T1) the weight gain was significantly (P < 0.0%) lower as compared to other treatments.